1998
DOI: 10.1016/s1044-0305(98)00109-3
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry for polymer analysis: solvent effect in sample preparation

Abstract: The success of matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry for the characterization of polymer structures and for the determination of average molecular weights and distributions depends on the use of a proper sample/matrix preparation protocol. This work examines the effect of solvents, particularly solvent mixtures, used to prepare polymer, matrix, and cationization reagent solutions, on MALDI analysis. It is shown that the use of solvent mixtures consisting of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…• Different baseline elevations in the low mass tail were described in literature due to different solvent mixtures [9] and due to different matrices as well [30]. The obtained MALDI mass spectra of this study confirm these observations.…”
Section: The Effect Of Mixing Ratiosupporting
confidence: 86%
See 1 more Smart Citation
“…• Different baseline elevations in the low mass tail were described in literature due to different solvent mixtures [9] and due to different matrices as well [30]. The obtained MALDI mass spectra of this study confirm these observations.…”
Section: The Effect Of Mixing Ratiosupporting
confidence: 86%
“…In recent years many factors influencing the quality of MALDI mass spectra of synthetic polymers were investigated especially factors of sample preparation. It has been shown that the matrix type, cationization reagent, their concentrations, as well as the type of solvent or solvent mixture, and the spotting technique affect the polymer distribution [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Besides sample preparation, the instrumentation parameters influence the determined molar mass distribution [17,18].…”
mentioning
confidence: 99%
“…Mass discrimination occurs with more broadly dispersed polymer samples such that the high molecular weight oligomers within the molecular weight distribution (MWD) are under-represented or not observed at all. Several reports have been written that hypothesize of the root cause for these discrimination effects [21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…These parameters, as well as laser energy, were most influential for the polystyrene with dithranol as the matrix. any factors influence the quality of matrixassisted laser desorption/ionization (MALDI) time-of flight (TOF) mass spectra of synthetic polymers [1][2][3][4][5][6][7][8][9][10][11]. Foremost is the nature of the sample itself.…”
mentioning
confidence: 99%
“…The detector voltage influences the sensitivity of the detector, but if the detector voltage is too high, a loss in the signal-to-noise may result because of the increase in background noise. To keep the design relatively simple and the amount of data to a minimum, we chose to concentrate on only two sample preparation parameters: matrix type and polymer concentration [6,8,10,21].…”
mentioning
confidence: 99%